2023
DOI: 10.7150/jca.79171
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of LncRNA UCA1 in Pancreatic Cancer: a mini-review

Abstract: Pancreatic cancer (PaC) is a common malignant tumor of the digestive tract, with a 5-year survival rate of less than 5% and high mortality rate in the world. LncRNAs have been showed to possess multiple biological functions in growth, differentiation, and proliferation, which play an important role in different biological processes and diseases, especially in the development of tumors. LncRNA UCA1, which is firstly identified in human bladder cancer, has been showed to be a tumor promoter in pancreatic cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“… 15 LncRNAs are involved in several physiological processes because they regulate gene expression at the epigenetic, transcriptional, and post-transcriptional levels. 16 Aberrant expression is also closely associated with tumor proliferation, differentiation, apoptosis, and metastasis. 17 The lncRNA MIR4435-2 host gene (MIR4435-2HG) is located on human chromosome 2q13.…”
Section: Introductionmentioning
confidence: 99%
“… 15 LncRNAs are involved in several physiological processes because they regulate gene expression at the epigenetic, transcriptional, and post-transcriptional levels. 16 Aberrant expression is also closely associated with tumor proliferation, differentiation, apoptosis, and metastasis. 17 The lncRNA MIR4435-2 host gene (MIR4435-2HG) is located on human chromosome 2q13.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sun et al. reviewed the functions and pointed out the importance of UCA1 in pancreatic cancer, who showed that UCA1 contributed to carcinogenesis, angiogenesis, and drug resistance via several signal pathways ( 13 ). Despite this, few details about UCA1 in pancreatic cancer are known, the regulatory role and mechanism of UCA1 are still unclear.…”
Section: Introductionmentioning
confidence: 99%